Medição e modelagem da erosão hídrica em sub-bacia hidrográfica com sistemas florestais - Silva, Bárbara Pereira Christofaro (2015)
The absence of political planning in natural resources uses have caused water erosion acceleration, pointed as one of the main causes of degradation and soils productivity loss, besides bringing problems regarding water quality and availability. The goals of the present work were to quantify, in the field, the soil and water losses caused by water erosion, in planted eucalyptus forests with different ages (EF1 and EF2), native forest (NF) and bare soil (BS); and to compare the erosion estimates using the USLE model, with topographic factors LSRUSLE e LSRUSLE3D, and the WEPP model, at the Terra Dura forest garden sub-basin, in the municipality of Eldorado do Sul – state of Rio Grande do Sul, Brazil. The soil losses were obtained through standard plots settled in Red Argisol, between the period of 2007 to 2012. To spatialize and estimate water erosion in all sub-basin’s area, USLE was applied through the Digital Elevation Model (DEM) and the spatialized maps of erosivity, erodibility, topographical factor, soil covering and conservation practices. The WEPP model was applied through the GeoWEPP software, using DEM and the sub-basin’s maps of soil and uses. It was observed the reduction of soil and water losses with the development of EF1 and EF2, approaching the values observed in NF. The soil losses for eucalyptus, observed in field, were down below the tolerance limit to the soil class studied, indicating the adequation of the management system. The sub-basin exhibited an erosivity mean of 4.183,4 MJ mm ha-1 h-1 yr-1, with the higher values occurring in the months of april, september and november. The erodibility of the main soil class, Red Argisol, was 0,0029 Mg h MJ-1 mm-1 and the C factor presented the values of 0,059, 0,016 and 0,017 for EF1, EF2 and NF, respectively. The USLE (LSRUSLE3D) estimated the higher value of soil loss mean in the Terra Dura sub-basin, followed by the USLE (LSRUSLE) and WEPP model. All of the models estimated soil losses for different soil uses in the following order: BS>EF1>EF2>FN. The USLE (LSRUSLE) presented the minor mean absolute deviation and estimated the nearest values to the field observations in all of the soil uses, followed by the WEPP model and the USLE (LSRUSLE3D).